TGFβ1 Induces Senescence and Attenuated VEGF Production in Retinal Pericytes - Dragana Avramovic; Sébastien A. Archaimbault; Alicia M. Kemble; Sabine Gruener; Mirjana Lazendic; Peter D. Westenskow (Biomedicines, 2022)
Diabetic retinopathy (DR) is a microvascular disease of the retina and a serious complication of type I and type II diabetes mellitus. DR affects working-age populations and can cause permanent vision loss if left untreated. The standard of care for proliferative DR is inhibiting VEGF. However, the mechanisms that induce excessive VEGF production in the retina remain elusive, although some evidence links elevated VEGF in the diabetic retina with local and systemic TGFβ1 upexpression. Here, we present evidence from animal models of disease suggesting that excessive TGFβ1 production in the early DR is correlated with VEGF mRNA and protein production by senescent pericytes and other retinal cells. Collectively, these results confirm that TGFβ1 is strongly implicated in the vascular complications of DR.